The Effects of Nano-SiO2 and Nano-TiO2 Addition on the Durability and Deterioration of Concrete Subject to Freezing and Thawing Cycles - Liu, Fang; Zhang, Tonghuan; Luo, Tao; Zhou, Mengzhen; Ma, Weiwei; Zhang, Kunkun (Materials, 2019)
The objective of this manuscript is to study the effects of nano-particle addition on the durability and internal deterioration of concrete subject to freezing and thawing cycles (FTCs). Fifteen nm of SiO2, 30 nm of SiO2, and 30 nm of TiO2 were added to concrete to prepare specimens with different contents. All the specimens were subjected to FTCs from 0 to 75. The mass of each specimen was measured once the FTCs reached 25, 50, and 75. Then the freezing and thawing resistance of the concrete was evaluated by computing the mass loss ratio. The pore fluid size distribution of the concrete was detected using nuclear magnetic resonance (NMR). The deterioration of the concrete subjected to FTCs was detected by industrial computed tomography (CT). The effect of different nano-particle sizes, different contents of nano-particles, and different types of nano-particles on the freezing and thawing resistance, the pore size, distribution, and the deterioration of the concrete were analyzed. The effects of FTCs on the pore size distribution and the internal deterioration of concrete were also studied. Compared to 30 nm-Nono-SiO2 (NS), 15 nm-NS had a better effect in improving the internal structure for concrete, and 30 nm-Nano-TiO2 (NT) also had a better effect in preventing pore and crack expansion.